2018
DOI: 10.1002/jbm.b.34202
|View full text |Cite
|
Sign up to set email alerts
|

Infection burden and immunological responses are equivalent for polymeric and metallic implant materials in vitro and in a murine model of fracture‐related infection

Abstract: The development of an infection is a major complication for some patients with implanted biomaterials. Whether the material or surface composition of the used biomaterial influences infection has not been directly compared for key biomaterials currently in use in human patients. We conducted a thorough in vitro and in vivo investigation using titanium (Ti) and polyether-ether-ketone (PEEK) as both commercially available and as modified equivalents (surface polished Ti, and oxygen plasma treated PEEK). Compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In the present iteration of the model, barium sulfate-enhanced PEEK gives good image quality and image processing is easily automated, making the model suitable for longitudinal studies. The use of PEEK also has clinical relevance, since it is increasingly used in orthopedic medicine and we have shown that the progression of infection around PEEK devices is essentially identical to titanium in a mouse model 23 . Using this model, non-infected rats display an uninterrupted progression of implant integration and bone remodeling, peak bone formation at day 14, and minimal periosteal reaction.…”
Section: Discussionmentioning
confidence: 94%
“…In the present iteration of the model, barium sulfate-enhanced PEEK gives good image quality and image processing is easily automated, making the model suitable for longitudinal studies. The use of PEEK also has clinical relevance, since it is increasingly used in orthopedic medicine and we have shown that the progression of infection around PEEK devices is essentially identical to titanium in a mouse model 23 . Using this model, non-infected rats display an uninterrupted progression of implant integration and bone remodeling, peak bone formation at day 14, and minimal periosteal reaction.…”
Section: Discussionmentioning
confidence: 94%
“…179 Once implanted, a bacterial culture is inoculated into the intraarticular space near the implant. 173 Implant-associated infection models have been established using a range of bacteria including Staphylococcus aureus and methicillinresistant S. aureus (MRSA), [32][33][34]36,115,117,128,134,[169][170][171][172][173][174][175][176][177][178][179][180][181][182]184,185 Staphylococcus epidermidis, 116 Escherichia coli, 163,180 Pseudomonas aeruginosa, 163 Propionibacterium acnes, 116,183 and Streptococcus agalactiae. 172 Bioluminescent strains of bacteria (e.g., S. aureus, E. coli) are frequently used to enable in vivo tracking and imaging of the extent and evolution of the infection over time.…”
Section: Considerations In Establishing Clinically Relevant Preclinic...mentioning
confidence: 99%
“…32,34,179,185 To measure and track the extent of the infection during and at the end of the study, in vivo bioluminescence imaging (BLI) of bacteria and colony forming unit (CFU) counts in excised bone and synovial tissue and on r e m o v e d i m p l a n t s h a v e b e e n a n alyzed. 12,32,33,36,[115][116][117]128,134,163,[170][171][172][173][174][175][176][177][178][179]182,183,185 Histology (e.g., hematoxylin and eosin, Gram stain, tartrate-resistant acid phosphatase (TRAP)) is performed on excised bone and synovial tissue to supplement CFU counts and to identify osteoclasts. 12,32,36,115,117,128,163,[169][170][171][172]174,[176][177][178][179]182,183,185 Scanning electron microscopy (SEM) and crystal violet staining are used to ...…”
Section: Considerations In Establishing Clinically Relevant Preclinic...mentioning
confidence: 99%
See 2 more Smart Citations